SIGNIFICANCE OF MICROBIAL PROCESSES IN GASES OF THE SOUTH CASPIAN BASIN - Katz B.J.; Narimanov A.; Huseinzadeh R. (My University, 2002)
The South Caspian basin has been a major petroleum-producing province for more than a century. While the basin's oil has been the focus of a number of studies the region's gas has been largely understudied. This study examines 31 gas samples from 14 fields with the primary purpose of determining their mode(s) of formation and the role that microbial activity has had in their formation and alteration.The basin's natural gas accumulations display significant differences in both molecular and isotopic composition. Gas wetness ranges from less than 1% at Absheron to greater than 12% at Guneshli. Methane carbon isotopic composition ranges from −57 to −37‰ relative to the PDB standard. The stable carbon isotopic composition of the wet gas (C2+) components also displays a very broad range (e.g. C2 ranges from −37 to −20‰; C3 ranges from −31 to −10‰; and nC4 ranges from −30 to −11‰).No strong depth-related trends were observed in any of the geochemical attributes. The absence of a trend implies that the gases have not been generated in situ but have migrated vertically, been altered, or represent a mixed product. Mixing is also suggested by the differences in the calculated thermal maturity levels between the C2+ components and methane. In some accumulations (e.g. Karabagly) as much as 55% of the methane may have a biogenic origin. These data further indicate that among the gas samples studied those from Bakhar appear to be the most mature, with thermal maturity values consistent with the ‘condensate-window’.In several fields, including Guneshli and Neftchala, the wet gas components display evidence for microbial alteration. This is largely manifested in anomalously heavy isotopic compositions of propane, n-butane, and n-pentane.